3(x-3)+2(x+2)=40

Simple and best practice solution for 3(x-3)+2(x+2)=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-3)+2(x+2)=40 equation:


Simplifying
3(x + -3) + 2(x + 2) = 40

Reorder the terms:
3(-3 + x) + 2(x + 2) = 40
(-3 * 3 + x * 3) + 2(x + 2) = 40
(-9 + 3x) + 2(x + 2) = 40

Reorder the terms:
-9 + 3x + 2(2 + x) = 40
-9 + 3x + (2 * 2 + x * 2) = 40
-9 + 3x + (4 + 2x) = 40

Reorder the terms:
-9 + 4 + 3x + 2x = 40

Combine like terms: -9 + 4 = -5
-5 + 3x + 2x = 40

Combine like terms: 3x + 2x = 5x
-5 + 5x = 40

Solving
-5 + 5x = 40

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 5x = 40 + 5

Combine like terms: -5 + 5 = 0
0 + 5x = 40 + 5
5x = 40 + 5

Combine like terms: 40 + 5 = 45
5x = 45

Divide each side by '5'.
x = 9

Simplifying
x = 9

See similar equations:

| Y=4x^3-3x^2 | | F(x)=x^3-4x^2-5x | | 7(p+2)=-4(-4p-8) | | -2(5x+1)=-3-3x | | 3(5n-5)=-90 | | 9c=5(101)-160 | | z-10=28 | | -8(4x-3)+6x=-158 | | -8(3x+1)+5x=87 | | 91=7(-5a-2) | | 2n/3=11 | | -6(3x+5)=60 | | (9*9)-(8+4)= | | -6k+15=-5k+2k | | -10-(-63)= | | -117+4x=12x+107 | | (-5)+x=32 | | 900t-10t^2=0 | | 4(5-4x)-3x=96 | | 2(5-2x)=1.2(3x-5) | | 4(5-4x)-3x=97 | | -6(3x+4)=30 | | 2u-9=-7u | | Tan63=X/4 | | 10x-93=-x+94 | | 3+.05(4a+8)=9-2a | | F(x)=12x-2y | | 20=k/2 | | h=900(t)-10(t^2) | | 4(3x+5)=6(2x+5)-10 | | 1/5(20a)=4–a | | 300+8x=20 |

Equations solver categories